The understanding about the concept of hibah among Malay language students, semester 5, Academy of Language Studies, UiTM Shah Alam / Muhamad Fahmi Mazzalan - Mazzalan, Muhamad Fahmi (2019)
Hibah is a contract used to show appreciation and love. The purpose of this study is to determine the level of understanding of Malay Language Students, Semester 5, Academy of Language Studies, UiTM Shah Alam about the concept of Hibah. This study focuses only on the semester 5 students. The total number of students involved is 65 peoples(population). The method used was quantitative through the set of questionnaires using google form help among students of the semester 5. The results showed that the semester 5 students of this program had a mid-level understanding of the concept of the Hibah based on the objectives of the study. In conclusion, it still needs a lot of effort to increase level of understanding and knowledge about Hibah concept, especially to the whole society.